Anti-Cholesterolemic Activity of Mulberry (Morus australis Poir) Ethanol Extract in Increasing HDL Levels and Inhibiting Formation of Foam Cells on Rat - Priska Ernestina Tenda; Eleonora Maryeta Toyo (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2021)
Mulberry leaves are one of the medicinal plants empirically used by people to reduce cholesterol levels. Previous study found that mulberry leaves contain flavonoids, act as cholesterol-lowering and tannins function to inhibit the absorption of food, including fat in the GI tract. The objective of this study is to determine the effect of mulberry leaf ethanol extract on increased HDL levels and to determine the inhibition of the formation of foam cells in male Wistar strain rats given the atherogenic diet. Thirty male Wistar rats were divided into six groups, which were normal group, negative control, positive control, and three groups of mulberry leaf extract at a dose of 25, 50, and 100 mg/200g BW rats, respectively. The HDL levels were measured pre- and post- treatment on days 0, 28, 35 and 42. The results showed that the most effective dose augmenting the HDL as well as inhibited the formation of aortic wall foam cell was the ethanol extract at a dose of 100 mg/200 g BW. In conclusion, mulberry leaves ethanolic extract have the potency to be developed as a natural cholesterol-lowering agent.